Purinergic signaling in atherosclerosis. Issue 3 (March 2015) - Ferrari, Davide; Vitiello, Laura; Idzko, Marco; la Sala, Andrea
Highlights Atherosclerosis is a leading cause of mortality. Purinergic signaling is involved in atherogenesis. Pro- and anti-atherosclerotic responses are mediated by extracellular nucleotides. Removing excess ATP and increasing adenosine is protective against atherosclerosis.